Pengaruh Laporan Pembiayaan Terhadap Kinerja Keuangan Bank Syariah Indonesia Periode 2016-2021 - Nadia Lara Sapitri; A. A. Miftah; Muhamad Subhan (Lembaga Pengembangan Kinerja Dosen, 2023)
The study aims to examine the effect of financing reports on financial performance at Pt Bank Syariah Indonesia Tbk for the 2016-2021 period. The independent variables used are Mudharabah Financing and Ijarah Financing while the Dependent Variables used are financial performance at Pt Bank Syariah Indonesia for the 2016-2021 period. The data used in this research is time series data in the form of Bank Syariah Indonesia's monthly Financial Statements from 2016-2021. So the population and sample are 12 X 6 = 72 samples, the sample is selected using the full sampling method. The analytical method used in this study is simple linear regression processed using SPSS 22 and Microsoft Excel 2016. The results of this study indicate that the independent variable mudharabah financing has a positive and significant effect on financial performance while ijarah financing has no significant effect on financial performance.